En jämförelse avseende beståndsgående-och stickvägsgående gallringsmaskiner - Jonsson, Mikael (2014)
The purpose of this report is to investigate and compare the difference between stand-thinning machines and strip-road thinning machines, and how they affect the stand on behalf of future growth, theoretical economic result, wind impact, snow pressure and density of stand. The investigation is regarding the first commercial thinning of pine stands, after pre-commercial thinning that was well conducted. The investigation area was located near Katrineholm, Sweden. The measurements that were measured were strength of thinning and amounts of wind throws, snow-breaks and hauling damages. The results that emerged, was that thinning with strip-road machines had a significantly higher strength of thinning over all, as compared with the stand- thinning machines (45 percent versus 30 percent). Comparisons between wind-throws, snow-breaks and hauling damages of the stand could not establish any significant differences between the two methods that were investigated. Conclusions, over all, were that if forest owners want to have more timber volume left for second thinning and final cut of the stand, the forest owners should choose the method with stand-thinning machines. From the point of view of gentle treatment of the stand and ground damages the choice should be the same. However, the method with strip-road thinning machines is the most common and accessible method in Sweden. Most likely it is the most economical way to manage the stand for forest owners in present time. If the method with stand-thinning machines is becoming more common in Sweden, it is suggested for forest owners to consider the stand-thinning method as a candidate for treatment due to economic aspects.